Progress of Ayush Sector in the Union Territory of Jammu And Kashmir During COVID-19 Pandemic (2020-2022) - A Review - Singh, Mohan; Parray, Mushtaq Ahmad; Hassan, Wahid ul; Mir, Aftab Iqbal; Gupta, Arun; Datta, Vishnu K; Khanna, Vishal; Khan, Imran; Rather, Aaqib H (International Research Journal of Ayurveda & Yoga, 2022)
COVID-19 pandemic and the lockdowns associated with it had an adverse effect on the functioning of all offices whether in Private/Public sector. This study titled “Progress of Ayush Sector in the Union Territory of Jammu and Kashmir during COVID-19 Pandemic (2020-2022)” was conducted with inputs from Directorate of Ayush, J&K, Medical Officers/Para Medical Staff working under the purview of Directorate of Ayush, J&K, Program Management Unit of National Ayush Mission, Civil Society members and common masses with the aim to observe the functioning and progress of Ayush sector in the Union Territory of Jammu & Kashmir during the COVID-19 pandemic. Ayush in Health care, Ayush for preventive measures during COVID-19 pandemic, infrastructural development in Ayush Sector, Promotive aspects, Ayush in public health programs, Medicinal Pants Sector were reviewed during this study. The review revealed that the Ayush sector in J&K showed tremendous growth with Ayush gradually becoming a house hold name and preferred mode of treatment for the people of J&K.